2021
DOI: 10.1109/access.2021.3119569
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Protein Interaction Prediction via Graph Signal Processing

Abstract: This paper tackles the problem of predicting the protein-protein interactions that arise in all living systems. Inference of protein-protein interactions is of paramount importance for understanding fundamental biological phenomena, including cross-species protein-protein interactions, such as those causing the 2020-21 pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Furthermore, it is relevant also for applications such as drug repurposing, where a known authorized drug is applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…where Mk is shown in (10). Notice that this update function not only adaptively updates based on the error, but also has a time-varying parameter M [k], which is different from the GLMS, the GNLMS, and the GLMP algorithms as they only adaptively update the error.…”
Section: Gnlmp Algorithm Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…where Mk is shown in (10). Notice that this update function not only adaptively updates based on the error, but also has a time-varying parameter M [k], which is different from the GLMS, the GNLMS, and the GLMP algorithms as they only adaptively update the error.…”
Section: Gnlmp Algorithm Derivationmentioning
confidence: 99%
“…Research in graph signal processing (GSP) has shown to be the solution to resolve the problem of processing irregular data by extending classical signal processing techniques such as Fourier transform and wavelet transform to graphs utilizing the spectral graph theory [1][2][3][4][5][6]. GSP-inspired ideas have a broad area of applications in various fields of study such as analysing brain signals [7], monitoring 5G Networks [8], modeling temperature data [9], making protien-protien interaction prediction [10], and modeling traffic events [11]. By defining graph convolution in neural networks using the Graph Fourier Transform (GFT), GSP has entered the field of deep learning; architectures such as the ChebNet and the graph convolutional network (GCN) are both deep learning architectures based on GSP backbones [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…RepGSP rewards links between “repulsive nodes” (i.e., nodes belonging to different communities). U 71 – 73 III. Factorization-based methods: factorize the network adjacency matrix to reduce the high-dimensional nodes in the graph into a lower dimensional representation space by conserving the node neighborhood structures.…”
Section: Introductionmentioning
confidence: 99%
“…It constructed an unsigned variational graph autoencoder, which combined the PPI network with amino acid sequence information to learn the features of proteins to predict PPI. Inspired by the methods of graph signal processing, Colonnese et al [25] considered node features on PPI networks as signals, and developed a Markov model to accomplish PPIs prediction. Lv et al [26] constructed a GNN-PPI model based on graph isomorphism network (GIN) to predict the interactions between protein-protein pairs.…”
Section: Introductionmentioning
confidence: 99%